2016
DOI: 10.1556/030.63.2016.001
|View full text |Cite
|
Sign up to set email alerts
|

Lectins and Tetrahymena – A review

Abstract: The unicellular ciliate Tetrahymena is a complete organism, one of the most highly developed protozoans, which has specialized organelles performing each of the functions characteristic to the cells of higher ranked animals. It is also able to produce, store, and secrete hormones of higher ranked animals and also react to them. It produces lectins that can bind them and has functions, which are influenced by exogenous lectins. The review lists the observations on the relationship between lectins and Tetrahymen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Surprisingly, we observed four distinct profiles of infectiveness: (i) productive cycle in permissive cells; (ii) abortive cycle; (iii) refractory cells; and (iv) most surprisingly, non-host cells exhibiting a cytotoxic phenotype in the presence of Tupanvirus without multiplication, a circumstance never previously reported—to the best of our knowledge (Supplementary table 1 ; Supplementary Notes 1). This latter profile was intriguing because toxicity was observed in Tetrahymena sp., a ravenous free-living protist 26 . This unusual phenotype was also observed in A. castellanii but only at higher multiplicities of infection (50 and 100; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, we observed four distinct profiles of infectiveness: (i) productive cycle in permissive cells; (ii) abortive cycle; (iii) refractory cells; and (iv) most surprisingly, non-host cells exhibiting a cytotoxic phenotype in the presence of Tupanvirus without multiplication, a circumstance never previously reported—to the best of our knowledge (Supplementary table 1 ; Supplementary Notes 1). This latter profile was intriguing because toxicity was observed in Tetrahymena sp., a ravenous free-living protist 26 . This unusual phenotype was also observed in A. castellanii but only at higher multiplicities of infection (50 and 100; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, hormones are synthesized, stored, and secreted by unicells which can influence phagocytosis [99,100] and there is a similar situation in multicells, where hormones which has specific functions (e.g., regulation of sugar metabolism, blood calcium level, ovarian cycle, etc.) are also influencing the phagocytosis of professional cells (macrophages and neutrophil granulocytes).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that Tetrahymena is able to use lectins to influence sexual reproduction, stimulate hormonal receptors, imitate hormonal functions, influence phagocytosis, cell movement and cell division [68]. Lectins are proteins found in plants and animals and are used to diagnose sugars in solutions or on the surface of cells, as well as in the study of blood groups.…”
Section: Hormone Receptorsmentioning
confidence: 99%